Academic Rumination, Decreased Working Memory Capacity, and Decisional Procrastination: An Experience Sampling Method (ESM) Approach to Measuring Negative Thought Intrusion - Eugenia Dhea Adeline; Akif Khilmiyah; Abd. Madjid (Journal of General Education and Humanities, 2026)
Negative thought intrusion among university students is a psychological condition that can interfere with cognitive performance and emotional well-being, particularly when influenced by maladaptive cognitive processes. This study aims to examine the effect of academic rumination, decreased working memory capacity, and decisional procrastination on negative thought intrusion among university students. This research employed a quantitative approach using the Experience Sampling Method (ESM). The study involved 20 respondents who completed repeated measurements at five time points, yielding 100 observational data points. Data were analyzed using multiple regression to determine the simultaneous and partial effects of the independent variables, and the coefficient of determination was used to assess the magnitude of their contribution to the dependent variable. The results indicate that academic rumination, decreased working memory capacity, and decisional procrastination simultaneously have a significant effect on negative thought intrusion, with a combined contribution of 88.9%. Partially, academic rumination shows the strongest influence, followed by decreased working memory capacity and decisional procrastination. These findings suggest that students with higher levels of rumination, reduced cognitive capacity, and a tendency to delay decision-making are more susceptible to negative thought intrusion. The study provides empirical evidence that can inform the development of cognitive and emotion regulation-based interventions for university students.